Program PKM Pengabdian Masyarakat : Sosialisasi Komik Edukasi Hukum Cambuk Solusi Pencegahan Jarimah di SMA Negeri 1 Kuta Makmur - Nur, Muhammad; H, Harun (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The Student Creativity Program (SKM) is is one of the efforts to foster, contain, and embody the creative as well as innovative ideas of students becoming a catalyst for improving the soft skills and competencies of Indonesian students. Students of Malikussaleh University in 2025 do PKM in the form of Socialization Comic Education Law Whip Prevention Solution in SMA Negeri 1 Kuta Makmur North Aceh Regency. The purpose of this program to introduce the penalty of whipping in the Acehnese Criminal Code to high school students, so as to avoid crimes. The activity began with providing socialization related to the Criminal Law, Sanctions and law enforcement processes, question and answer sessions and discussions. The results of this activity has had a positive impact in the form of increasing the knowledge of participants in understanding the essence of whipping contained in the Criminal Code of Aceh. This volunteer activity not only provides direct benefits to partners in the short term, but also creates a sustainable impact in understanding whatever prohibited crimes regulated in the Criminal Law of Aceh.